Effect of cognitive multisensory rehabilitation on upper extremity function in stroke patients: A randomized controlled trial - El-Din Mahmoud, Lama Saad; Mohamed, Omnia Shokry; Yacoub, Osama; Sadik Badawy, Mohammad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to examine the impact of upper extremity (UE) rehabilitation based on neurocognitive multisensory therapy in stroke patients, focusing on assessing its effects on the recovery of UE function and suggesting it as a post-stroke therapeutic method. The study was conducted as a randomized, prospective, controlled trial with a pre- and post-experimental design. Thirty stroke patients were equally divided into study and control groups and evaluated before and after treatment. Outcome measures included the Action Research Arm Test (ARAT), Manual Function Test (MFT), Motor Evaluation Scale for Upper Extremity in Stroke Patients (MESUPES), and Fugl Myer Assessment upper extremity (FMA-UE). Both groups received a specific physiotherapy program, while the study group also received Cognitive Multisensory Rehabilitation (CMR). All analyses were performed using SPSS (version 25). There were no significant differences between the groups in age, weight, height, BMI, duration of illness, MMSE, sex, or spasticity grade distribution (p > 0.05). Post-treatment comparison between both groups showed a statistically significant increase in the ARAT, MFT, MESUPES, and FMA-UE scores in the study group compared to the control group (p < 0.05). For stroke patients, CMR intervention is considered a beneficial neuro-rehabilitation strategy for enhancing upper extremity sensorimotor capabilities through physical therapy.